Materials that Move Smart Materials, Intelligent Design - Bengisu, Murat (PoliMI SpringerBriefs,, 2018)
This book presents a design-driven investigation into smart materials developed by chemists, physicists, materials and chemical engineers, and applied by designers to consumer products, buildings, interfaces, or textiles. Introducing a class of smart materials (referred to as stimuli-responsive, morphing or kinetic materials) that move and change their shape in response to stimuli, the book presents their characteristics, advantages, potentials, as well as the difficulties involved in their application. The book also presents a large number of case studies on products, projects, concepts, and experiments employing smart materials, thus mapping out new design territories for these innovative materials. The case studies involve different fields of design, including product, interior, fashion, and communication design. Reflecting the growing demand for sustainable and human-centered design agendas, the book explores and reveals the role and influence of these new materials and technologies on design and human experience, and discusses how they can be used to redefine our objects and spaces so as to promote more resilient environments. The book offers an intriguing and valuable resource for design professionals, engineers, scientists and students alike. .